2020
DOI: 10.1186/s12887-020-02129-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of time under mechanical ventilation on bronchopulmonary dysplasia severity in extremely preterm infants: a pilot study

Abstract: Background: The relation between mechanical ventilation (MV) and bronchopulmonary dysplasia (BPD)-a common disease in extremely premature newborn (PTNB)-is well stabilished, but is unknown, however, how much time under MV influences the severity of the disease. Aim: To define the duration under MV with greater chance to develop moderate to severe BPD in extremely PTNB and to compare clinical outcomes before and during hospitalization among patients with mild and moderate to severe BPD. Methods: Fifty-three PTN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
1
9
1
Order By: Relevance
“…The differences in that study with the current whole‐population study might be explained by a larger variation of clinical practice and the smaller gestational age of the included infants in the current whole‐population study. Escobar et al recently studied 53 extremely premature infants and reported that a duration of ventilation exceeding 36 days was related to a greater chance of developing moderate‐to‐severe BPD, a finding which was consequently confirmed in a small validation sample of 16 extremely preterm infants 17 . In that smaller study, however, the prediction time point was relatively late in postnatal life compared with our study (36 compared to 8 days).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The differences in that study with the current whole‐population study might be explained by a larger variation of clinical practice and the smaller gestational age of the included infants in the current whole‐population study. Escobar et al recently studied 53 extremely premature infants and reported that a duration of ventilation exceeding 36 days was related to a greater chance of developing moderate‐to‐severe BPD, a finding which was consequently confirmed in a small validation sample of 16 extremely preterm infants 17 . In that smaller study, however, the prediction time point was relatively late in postnatal life compared with our study (36 compared to 8 days).…”
Section: Discussionsupporting
confidence: 82%
“…Escobar et al recently studied 53 extremely premature infants and reported that a duration of ventilation exceeding 36 days was related to a greater chance of developing moderate-to-severe BPD, a finding which was consequently confirmed in a small validation sample of 16 extremely preterm infants. 17 In that smaller study, however, the prediction time point was relatively late in postnatal life compared with our study (36 compared to 8 days). Our results are also in agreement with Jensen et al who studied 3,343 extremely low-birthweight infants and reported that among the survivors, exposure to a greater number of mechanical ventilation courses was associated with a progressive increase in the risk of BPD and use of supplemental oxygen at discharge.…”
Section: Discussioncontrasting
confidence: 72%
“…Mechanical ventilation has been shown to increase the risk of BPD, mortality rates, the need for oxygen after discharge, and rates of other complications such as periventricular leukomalacia and retinopathy of prematurity 16,20. A longer cumulative duration of mechanical ventilation has been found to have the greatest impact on BPD rates, supporting the practice of early extubation trials, even if the infant might ultimately need to be reintubated 16,21. Noninvasive ventilation can be used successfully in the delivery room for very premature infants and can decrease BPD rates, even if intubation is needed at a later time 21,22.…”
Section: Available Knowledgementioning
confidence: 96%
“…In preterm neonates with extremely low birth weight exposed to more than six weeks of MV, mortality risk increases 8-fold. The risk rises by thirteen times when stratified for only cardiorespiratory causes [27]. Every extra week a neonate spends on MV raises the risk of developing BPD by 2.7 fold.…”
Section: Mechanical Ventilation (Mv)mentioning
confidence: 99%